2021
DOI: 10.7197/cmj.973939
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Women during COVID-19 pandemic: A Hospital-Based, Prospective, Cross-sectional Comparative Study

Abstract: International studies have shown that overall sexual activity and frequency of sexual intercourse decreased significantly during the COVID-19 pandemic. The aim of this study is to compare the female sexual dysfunction (FSD) rate in women during the COVID-19 pandemic in tertiary hospital in Turkey. Method: A total of 150 participants who were 50 pregnant women (group I), 50 healthcare women (group II) and 50 other women (group III), participated in study. A female sexual function index (FSFI) questionnaire was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Research conducted on pregnant women in Iran also showed that higher gestational age was associated with a higher prevalence of sexual dysfunction (24). In Turkey, healthcare staff reported better sexual function scores throughout the COVID-19 crisis than pregnant and other women (P = 0.001) (15). A study conducted on 200 Chinese couples showed that the overall score of sexual function was lower in the women with azoospermia husbands than the women with normal husbands (25.12 ± 5.56 vs. 26.75 ± 4.82, t = -2.22, P = 0.03) (31).…”
Section: Influential Factors In Female Sexual Function Throughout The...mentioning
confidence: 91%
See 1 more Smart Citation
“…Research conducted on pregnant women in Iran also showed that higher gestational age was associated with a higher prevalence of sexual dysfunction (24). In Turkey, healthcare staff reported better sexual function scores throughout the COVID-19 crisis than pregnant and other women (P = 0.001) (15). A study conducted on 200 Chinese couples showed that the overall score of sexual function was lower in the women with azoospermia husbands than the women with normal husbands (25.12 ± 5.56 vs. 26.75 ± 4.82, t = -2.22, P = 0.03) (31).…”
Section: Influential Factors In Female Sexual Function Throughout The...mentioning
confidence: 91%
“…The main risk factors for reducing female sexual function mentioned in the studies were anxiety (n = 8), depression (n = 5), unemployment or variable employment status (n = 5), lower level of income or economic status (n = 3), older age (n = 3), and fear (n = 3). The education level was examined in 5 studies, 3 of which reported a relationship between a lower level of education and lower scores of sexual function (15,33,34); nevertheless, 2 articles reported such a relationship for university education (5,20). Multiparity and pregnancy were associated with less female sexual function in 2 (5, 20) and 3 (16,20,34) studies, respectively.…”
Section: Influential Factors In Female Sexual Function Throughout The...mentioning
confidence: 99%